Sonographic Evaluation of the Anterolateral Ligament of the Knee: A Cadaveric Study - Zappia, Marcello; Oliva, Francesco; Chianca, Vito; Di Pietto, Francesco; Maffulli, Nicola (The Journal of Knee Surgery, 2019)
Rotational stability of the knee involves not only the cruciate ligaments but also another structure named anterolateral ligament (ALL), the function of which is still controversial. This study evaluated the effectiveness of high-resolution ultrasound (US) examination to detect the ALL. We studied 8 cadaveric knees (8 ALLs). On each knee, high-resolution real-time ultrasonography examination was performed by an experienced musculoskeletal radiologist before and after the procedure, with the surgeons blind to the results of the scan both before and after dissection. The ALL was identified in each cadaver limb by the musculoskeletal radiologist. US is a useful imaging modality to identify and evaluate the ALL. The ability of US to fully evaluate injuries involving the ALL still needs to be demonstrated in a clinical setting.
Keywords: ultrasonography; anterolateral ligament; knee; rotational stability; anterior cruciate ligament